Potential data ownership systems - Fraioli, Gianni (2023)
This work proposes to unravel the discussion regarding the administration of digital data generated freely by the users. In order to do so, we will present three potential data ownership systems: private ownership, based on the implementation of a free data-market; public ownership, where the state administers the data flows; finally, the communitarian approach, where the control of the data flow rests under the supervision of smaller political communities. The three systems will perform as «Ideal Types» (Weber, 1985), useful to synthesize similar approaches at the moment scattered due to a lack of a sufficiently developed theoretical corpus. Methodologically, this tripartite taxonomy allows us to highlight the range and limitations of some of the proposals of various authors, as well as serve as the prologue for the presentation of an alternativethat we deem superior.